Informativeness of accounting earnings in family firms - DOMINGO JAVIER SANTANA MARTÍN; JERÓNIMO PÉREZ ALEMÁN; CAROLINA BONA SÁNCHEZ (Management Letters/Cuadernos de Gestión, 2009)
This work examines the relationship between the family control and informativeness of accounting earnings in listed non-financial Spanish companies between 1997 and 2003. The results reveal a negative relationship between the family nature of the controlling shareholder and the credibility of accounting information. Moreover, as the level of voting rights in the hands of the family ultimate owner increases, the informativeness of earnings decreases. Only in family firms where the CEO is hired, the family nature affects positively on the informativeness of accounting earnings.